(3eHdZ GdeCehd Ydi bhGYO GdCUhds - (3GdeNJGQ Hf HhfG,J (B1220 (3g` s ((3ehQjJGfjG s)
(3ChdgG (B:s
(3GdMeO ddg Ydi CUhd eBNP Gdabg ef GdQShd hef SfG CUhdg JabgG Yf GdgOi ef fhQg JfHgG s
(3BNQgG (B:s
(3hfLMJ HGdUOb Cgd GdUOb hhKbJ HGdMb Cgd GdMb s
(3GdfSNI HgG MhGTs
(3fSNI eYfhfg HGdMHQ GdCMeQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdeYgO GdehQjJGfi ddHMK GdYdei (B((3abg eGdci (B79) s
Keywords: (3Gdabg GdeGdcjs